Role of local culture, religion, and human attitudesn in the conservation of sacred populations of a threatened ‘pest’ species (2014)
Indigenous belief systems and informal institutions that result in the conservation of wild species or sites exemplify biocultural conservation. The erosion of cultural beliefs and practices can have adverse, often severe, consequences for biodiversity. We explored the relationships among informal institutions, religion, and human attitudes toward sacred populations of a threatened, endemic species, Sclater’s monkey (Cercopithecus sclateri), in two communities in southeastern Nigeria. Due to habitat loss and hunting pressure across the species’ range, monkeys in these two sites live alongside people, raid farms and gardens, and are commonly viewed as pests. Using structured (n = 410) and semi-structured (n = 21) interviews, we examined factors influencing residents’ views of the monkeys, mechanisms affecting adherence to social taboos against harming monkeys, and implications for conservation. Our analyses revealed that most residents, particularly those from one community, women, and farmers, held negative opinions of the monkeys. Crop and garden raiding by monkeys had the most adverse effect on people’s attitudes. Although the adoption of Christianity weakened residents’ views regarding the no-killing taboos, continued adherence to the taboos was particularly influenced by supernatural retribution in one site and community disapproval in the other. Only one community widely conferred symbolic importance on the monkeys. Such site differences illustrate the value of local cultural understanding in conservation. Pre-intervention studies of this nature allow for the development of locally and culturally sensitive conservation programs, as well as better-informed assessments of what interventions are most likely to be effective.